Design and characterization of hybrid hemp/carbon laminates with improved impact resistance. (2021) - De Fazio, Dario; Cuomo, Stefano; Boccarusso, Luca; Pinto, Fulvio; Durante, Massimo; Meo, Michele
Abstract: Thanks to their mechanical properties and lightness, composite materials, are widely used as structural parts in marine, automotive and aerospace. However, even though they are characterised by high in-plane properties, their out of plane performances are not remarkable, therefore during operating conditions, they can be involved in accidental impacts by runaway debris or tool drop in maintenance operations that can cause barely visible impact damage (BVID). This type of damage is usually related to a particular category of impact events defined as Low Velocity Impact (LVI), characterised by velocities up to 10 m/s [1] . In order to overcome the aforementioned low impact resistance of composites, research is focused on improving the damage tolerance of this class of materials. One solution proposed in literature is the hybridisation process that merges synthetic and natural fibres aiming to obtain a composite with good in-plane and out-of-plane properties [2, 3], improving impact performance while guaranteeing resistance and stiffness due to the higher modulus of the synthetic fibres. The aim of this work is to evaluate the impact behaviour of Hemp-Carbon composite panels manufactured by hybridisation, under LVI events. Damping tests and low velocity impact tests at 10 J and 20 J were carried out in order to evaluate the Hybrid configuration damping properties and impact behaviour. Moreover, in order to have a better understanding of the internal damage for each impact energy, non-destructive analyses were performed. Results showed improved damping properties for the Hybrid configuration, which is characterised by a more ductile behaviour if compared to traditional Carbon fibre reinforced polymers (CFRP). Non-destructive tests carried on the Hybrid composite showed, at the same absorbed energy level, a smaller extension of the damaged area (−40% at 10 J and −10% at 20 J) localised at the interface between hemp and carbon fibres.